A comparative study on clinical and serological characteristics between patients with rhupus and those with systemic lupus erythematosus and rheumatoid arthritis. (September 2020) - Frade-Sosa, Beatriz; Narváez, Javier; Salman-Monte, Tarek Carlos; Castellanos-Moreira, Raul; Ortiz-Santamaria, Vera; Torrente-Segarra, Vicenç; Castellvi, Ivan; Magallares, Berta; Reina, Delia; Minguez, Sonia; Sallés, Meritxell; Manrique de Lara, Maria García; et al.
Background: The concomitant presence of two autoimmune diseases – systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) – in the same patient is known as rhupus. We evaluated a group of patients with rhupus to clarify further their clinical, serological and immunogenic features in a multi-centre cohort. In addition, the study aimed to explore the utility of the 2019 European League Against Rheumatism/American College of Rheumatology (EULAR/ACR) SLE classification criteria in our group of patients with rhupus. Methods: This was a cross-sectional study. We included rhupus patients from 11 different rheumatology departments, and compared them to SLE and RA patients at a ratio of 2:1. All information was recorded following a pre-established protocol. Results: A total of 200 patients were included: 40 rhupus patients and 80 each of SLE and RA patients as controls. Disease duration was similar among SLE and rhupus groups (around 13 years), but the RA group had a significantly lower disease duration. Main clinical manifestations were articular (94.2%), cutaneous (77.5%) and haematological (72.5%). Rhupus patients had articular manifestations similar to those expected in RA. Only 10% of rhupus patients had renal involvement compared with 25% of those with SLE ( p < 0.05), while interstitial lung disease was more common in patients affected by RA. The 2019 EULAR/ACR SLE criteria were met in 92.5% of the rhupus patients and in 96.3% of the SLE cohort ( p > 0.05). Excluding the joint domain, there were no differences between the numbers of patients who met the classification criteria. Conclusion: Rhupus patients follow a particular clinical course, with full expression of both SLE and RA in terms of organ involvement, except for a lower prevalence of kidney affection. The new 2019 EULAR/ACR SLE criteria are not useful for differentiating SLE and rhupus patients. A new way of classifying autoimmune diseases is needed to identify overlapping clusters.